Processo de cuidar em instituições de longa permanência de idosos: (re)pensando a função dos cuidadores - Medeiros, Fabíola de Araújo Leite (2014)
Introduction: This work arises from the need for recognition of the care process in Long-Term Care Institution (LTCI) seeking improvements to the standard of care support network for institutionalized elderly. Purpose: To analyze the process of care in a LTCI, aiming to (co)structuring of care based on practical knowledge of the socialization of elderly caregivers and Cáritas Clinical Process. Method: Converged Care Research (CCR).performed in a LTCI in Campina Grande/PB in the period of June to November 2013, with the participation of 18 caregivers. Data collection took place following the phases of the PCA, and the instruments were used for data collection: two semi-structured questionnaires and ten scripts used in meeting titled as workshops for caregivers of the elderly. Through content analysis was possible to list the themes related to the care process based Cáritas Clinical Process. The project followed the ethical recommendations and was approved under protocol n. 18413413.3.0000.5187. Results: The results allowed us to describe and analyze the process of care in the LTCI, as well as the profile of caregivers of elderly motivations that forwarded the letter to the institution, description of activities and difficulties experienced in the service routine. There was possible (co) design a care process based Cáritas Clinical Process (CCP), which were listed the factors of care exercised by caregivers: 1) Caregivers practice love, kindness and fairness; 2) Caregivers describe its authenticity with their tools ; 3) Caregivers try to cultivate self care practices to yourself and to each other; 4) Caregivers help develop confidence in transpersonal caring; 5) Perception of caregivers of elderly in relation to positive and negative feelings; 6) Caregivers using creativity and knowledge to know is, how to do, learn to understand and know how to live; 7) Engaging caregivers on experiences of genuine teaching and learning; 8) Caregivers attempt to provide an environment for the care of institutionalized elderly; 9) Caregivers help in satiation of basic needs with the intention of caring; 10) Perceptions of elderly caregivers about the mysteries of life and death. Conclusions: It is concluded that the process of care in the LTCI has attributes that drive a humanistic system of action oriented transpersonal relationship between caregivers and elderly. It was possible to measure the effectiveness of the CCP through the proposal of care exercised daily by workers who work at the institution weaving rethinking the role of these workers that use of empiricism and creativity among their care practices. Also showed the importance of the use of Science in Nursing preparation of the whole study. It is assumed that this study is useful for the social recognition of the care in LTCI process of rethinking the role of caregivers for the elderly in institutions, to foster future research related to LTCI and the elderly, and especially for public institutions, seeking assistance for improvements to its residents.